1993
DOI: 10.2220/biomedres.14.191
|View full text |Cite
|
Sign up to set email alerts
|

<b>MAJOR KININASES IN RAT URINE ARE NEUTRAL ENDOPEPTIDASE AND CARBOXYPEPTIDASE Y-LIKE </b><b>EXOPEPTIDASE </b>

Abstract: Two types of kininases were separated from rat urine by gel-filtration on a column of Superdex 200 and characterized as a membrane-bound neutral endopeptidase (EC 3.4.24. ll) and a carboxypeptidase Y-like exopeptidase. The neutral endopeptidase which was found in a void volume fraction, liberated first Pheg-Arg9 and then Phe5-Serf-Pro? from bradykinin (BK)*. The kininase activity was inhibited by phosphoramidon and thiorphan but not by captopril. Another kininase with an apparent molecular weight of 93,000 cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…According to the aforementioned results (Section I.B.4), the major kininases in urine collected from the rat ureter are CPY-like endopeptidase and NEP (Kuribayashi et al, 1993). In human urine, these two peptidases are also major kininases, but the contribution of kininases is dependent on the pH of the urine; therefore, NEP is more active at a neutral pH, whereas CPY is active at both neutral and acidic pH values, as demonstrated by the effects of inhibitors on each enzyme (Saito et al, 1996).…”
Section: Renal Kininase Lnhibitonmentioning
confidence: 96%
“…According to the aforementioned results (Section I.B.4), the major kininases in urine collected from the rat ureter are CPY-like endopeptidase and NEP (Kuribayashi et al, 1993). In human urine, these two peptidases are also major kininases, but the contribution of kininases is dependent on the pH of the urine; therefore, NEP is more active at a neutral pH, whereas CPY is active at both neutral and acidic pH values, as demonstrated by the effects of inhibitors on each enzyme (Saito et al, 1996).…”
Section: Renal Kininase Lnhibitonmentioning
confidence: 96%
“…A microdissection technique performed in the individual nephrons revealed that kininase activity is present not only in the proximal tubules, but also in the medullary CD (108). We identified carboxypeptidase Y-like exopeptidase (CPY) and neutral endopeptidase (NEP) as major kininases in rat urine (110). Carboxypeptidase Y was originally found in yeast.…”
Section: Kininasesmentioning
confidence: 99%
“…This suggests that EB is a candidate for a new type of diuretic and natriuretic agent. NEP and CPY-like exopeptidase in rat urine were sepa rated by using a Superdex 200 column as described in the previous paper (3). Plasma samples were prepared from blood collected from the carotid artery under ether anesthesia (2).…”
mentioning
confidence: 99%
“…Enzyme activities of isolated CPA, CPB and CPY were determined with peptide substrates: Z-Gly Phe for CPA (5), Bz-Gly-Arg for CPB (6) and Z-Phe-Leu for CPY (7). Assays of kininase activity and detection of BK fragments were carried out by HPLC (2,3). The in vivo effects of EB were studied in male Sprague-Dawley strain rats (SPF, 280-350g, 8 to 10-week-old, anesthetized with sodium pentobarbital, 40 mg/kg, i.p.).…”
mentioning
confidence: 99%